Outcomes of Children Treated with Short vs. Long Course Parenteral Antibiotic for Acute Hematogenous Osteoarticular Infections. (4th October 2017) - Otto, William; Kramer, Michael; Helal, Asad; Jackson, Mary Anne; Myers, Angela
Abstract: Background: In pediatric osteoarticular infections (OAI), antibiotics are given intravenously (IV) until clinical improvement, then completed with oral antibiotics. Adverse events (AE) associated with therapy and specific markers to guide transition are not well studied. We sought to determine the impact on OAI outcome with early transition to oral antibiotic therapy guided by clinical response and use of C-reactive protein (CRP) levels. Methods: Clinical course and AE were reviewed in a retrospective analysis from 2010 to 2015 at our hospital. CRP level prior to transition to oral antibiotics was analyzed at 3 different levels: <3 mg/dL, <5 mg/dL, and 50% decrease from the peak. Development of long-term sequelae (limp, limb deformities or chronic infection) and re-hospitalization was assessed. Results: 1004 cases of OAI were confirmed. Subacute presentations or chronic conditions were excluded. 352 cases were identified; median age 7.5 years (IQR 2.5–11.0); 65% male. 266 patients received <7 days of IV antibiotics vs. 86 that received >7 days. Clinical features are seen in Table 1. 337 patients were discharged with oral therapy. CRP analyses are shown in Figure 1. Transition to oral antibiotics with a CRP <5 mg/dL was associated with a significant decrease in the odds of developing long-term sequelae. No decrease was seen with CRP <3 mg/dL or a CRP decrease by 50%. Conclusion: Children with uncomplicated OAI who received short-course IV prior to oral transition developed adverse outcomes infrequently. A CRP of <5 mg/dL may be a safe set-point to transition to oral antibiotics. Larger, prospective studies are needed to evaluate the impact of transition to oral antibiotics on the development of sequelae. Disclosures: All authors: No reported disclosures.